Strategi Kepala Madrasah Dalam Peningkatan Budaya Bersih Di MA Ar-Rahman Sumoyono Diwek Jombang - Binti Masrufa; Windi Qomaria (At Tadbir: Islamic Education Management Journal, 2023)
This study aims to describe the strategies of the headmaster of madrasas in improving clean culture and what the supporting and inhibiting factors are in improving clean culture at MA Ar-Rahman Sumoyono, Diwek, and Jombang This research method is qualitative field research. This study uses a qualitative descriptive research design. Data collection techniques include structured interviews, participatory observation, and documentation. Then the data wettability test was carried out by extending observations, triangulation, and peer discussions. Followed by data analysis, namely data reduction, data display, and conclusion drawing or verification. The results showed that increasing the culture of cleanliness by implementing the Clean Saturday program has gone quite well by observing the active participation of madrasa residents, providing motivation to build awareness in maintaining cleanliness, and being supported by adequate cleaning tools. The inhibiting factors in this program are the different levels of student understanding of directions and student awareness in caring for cleaning tools, which are still lacking.